Exploring muslim taxpayers’ intentions to reduce tax liability through zakat rebates - Muhammad, Izlawanie; Mohamad Nor, Nur Shahira (Proceeding International Conference on Accounting and Finance, 2024)
This study investigates the impact of Malaysia’s zakat rebate system, introduced in 2001 as part of the individual tax framework, wherein Muslim taxpayers can reduce their tax obligations by claiming zakat payments as a deductible tax rebate. While this approach encourages increased zakat contributions, it poses a potential challenge by reducing overall tax revenue. The research aims to explore the intentional motivations of Muslim taxpayers in enhancing their zakat payments to decrease their tax liability concurrently. This study employed a quantitative methodology by distributing questionnaires to Muslim zakat contributors and taxpayers who claimed the zakat rebate. The findings highlight a common intention among respondents to intentionally increase zakat payments as a strategic means to lower their tax liability. The results shed light on the intricate relationship between religious obligations and fiscal incentives embedded within the tax system. The findings also contribute to the broader discussions on the social and economic implications of integrating religious principles into contemporary tax systems, opening avenues for further research and dialog in this interdisciplinary field.